Implementasi Pemikiran KH. Muhammad Arwani Amin Dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Santriwati JQH UNIA Prenduan - Afifah, Afifah; Puteri, Shilviana Helmalia; Wardi, Moh (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
KH. Muhammad Arwani Amin is one of the leading scholars of Qur'an memorization in the archipelago. The influence of his thoughts is very large can be observed since the establishment of Pondok Yanbu'ul Qur'an increasingly mushrooming Pondok Tahfidzul Qur'an throughout the archipelago that applies his thoughts, especially the JQH UNIA Prenduan tahfidz program. Jam'iyyatul Qurro' Wal Huffadz is one of the superior non-academic programs for UNIA intensive program students which was officially established in 2018 under the auspices of PP. Al-Amien Prenduan. The problem in this study is how the UNIA JQH program implements KH. Arwani's thoughts and what are the supporting factors as well as obstacles to the implementation of KH. Arwani's thoughts in the program. The purpose of this study is to describe the implementation of KH. Arwani's thoughts in the JQH program and describe the supporting factors as well as the obstacles to the implementation of KH. Arwani's thoughts in the program. The approach in this research is descriptive qualitative. The results of this study indicate that the UNIA JQH program implements KH. Arwani's thoughts as guidelines or alternatives to answer the various challenges of female students in memorizing the Qur'an. This can be observed from the concept and method of memorizing the Qur'an, Adab and the application of memorizing the Qur'an with a sorogan system. And the supporting factor is the regulations that are implemented. While the obstacle is the lack of time allocation for special activities for the JQH program on the sidelines of the Ma'had and UNIA Campus activity schedules.